Metacognition fosters cultural learning : evidence from individual differences and situational prompts. - Morris, Michael W. (2020)
We investigated the role of metacognition in the process by which people learn new cultural norms from experiential feedback. In a lab paradigm, participants received many trials of simulated interpersonal situations in a new culture, each of which required them to make a choice, and then provided them with evaluative feedback about the accuracy of their choice with regard to local norms. Studies 1 to 3 found that participants higher on an individual difference dimension of metacognitive proclivity learned to adhere to the local norms faster. This relationship held up in simple and complex situations, that is, when the feedback was noisy rather than completely reliable, and it also held up when possibly confounding individual differences were controlled (Study 2). Further evidence suggested that the underlying mechanism is the largely implicit process of error monitoring and reactive error-based updating. A measure of surprise (an indicator of error monitoring) mediated the link between metacognitive proclivity and faster learning (Study 3). In experiments that varied the task so as to afford different kinds of metacognitive processing, participants learned faster with posterror prompts but not with postaccuracy prompts (Study 4). Further, they learned faster with nondirected prompts that merely provided a break for processing rather with prompts that directly instructed them to reason explicitly (Study 5). We discuss the implications of these findings for models of culture, first- and second-culture learning, and for training and selecting people for foreign or intercultural roles.